THE INFLUENCE OF SCHOOL SOCIAL ENVIRONMENT ON STUDENT LEARNING MOTIVATION AT SMA NEGERI 1 LAWA - Ardi Gunanta Sembiring (Prodi Bimbingan Konseling Universitas Negeri Manado, 2022)
This study aims to determine the effect of the school's social environment on student motivation in SMA Negeri 1 Lawa in the academic year 2020/2021. This research uses quantitative research methods. The population was 649 students and the sample was 10% or as many as 65 students. The data collection technique used a questionnaire with a Likert scale. Based on data analysis using simple linear regression analysis with the help of a computer program SPSS 23 for windows, it shows that there is an influence of the school social environment on student learning motivation. It is obtained by the regression equation Ŷ = 43,292 + 0.465 X with the quantitative increment ratio of the two variables is 1: 0.465, this comparison shows that if there is an increase of one time / unit in the school social environment variable (X) there will be an increase of 0.465 in the Student Learning Motivation variable (Y). The regression equation is significant or will not be tested using the Fcount value at the significant level of 0.05. Meaning that Ha was accepted and Ho was rejected. The conclusion is that the hypothesis that says there is an effect of school social environment on student learning motivation at SMA Negeri 1 Lawa is accepted and significant, this is indicated by the value of the regression coefficient (F) of 18,458 with a significant 0,000.